Critical zone structure controls concentration‐discharge relationships and solute generation in forested tropical montane watersheds. Issue 7 (31st July 2017) - Wymore, Adam S.; Brereton, Richard L.; Ibarra, Daniel E.; Maher, Kate; McDowell, William H.
Abstract: Concentration‐discharge (C‐Q) relationships are poorly known for tropical watersheds, even though the tropics contribute a disproportionate amount of solutes to the global ocean. The Luquillo Mountains in Puerto Rico offer an ideal environment to examine C‐Q relationships across a heterogeneous tropical landscape. We use 10–30 years of weekly stream chemistry data across 10 watersheds to examine C‐Q relationships for weathering products (SiO2 (aq), Ca 2+, Mg 2+, and Na + ) and biologically controlled solutes (dissolved organic carbon [DOC], dissolved organic nitrogen [DON], NH 4 +, NO 3 –, PO 4 3 –, K +, and SO 4 2 – ). We analyze C‐Q relationships using power law equations and a solute production model and use principal component analysis to test hypotheses regarding how the structure of the critical zone controls solute generation. Volcaniclastic watersheds had higher concentrations of weathering solutes and smaller tributaries were approximately threefold more efficient at generating these solutes than larger rivers. Lithology and vegetation explained a significant amount of variation in the theoretical maximum concentrations of weathering solutes ( r 2 = 0.43–0.48) and in the C‐Q relationships of PO 4 3 – ( r 2 = 0.63) and SiO2 (aq) ( r 2 = 0.47). However, the direction and magnitude of these relationships varied. Across watersheds, various forms of N and P displayed variable C‐Q relationships, while DOC was consistently enriched with increasing discharge. Results suggest that PO 4 3 – may be a useful indicator of watershed function. Relationships between C‐Q and landscape characteristics indicate the extent to which the structure and function of the Critical zone controls watershed solute fluxes. Key Points: C‐Q relationships are analyzed from 10 watersheds to understand how the Critical Zone controls solute generation in a tropical landscape Landscape characteristics explained a significant amount of variation in the C‐Q relationships of PO 4 3 − and SiO 2 − PO 4 3 − may be a useful indicator of watershed function